The Great EU Debt Write-Off: A Classroom Simulation. (August 2016) - Evans, Anthony J.; Tse, Terence; Baker, Jeremy
Background. When one economic entity is both a creditor and debtor to another economic entity, a somewhat obvious and simple resolution is to cross-cancel their debts. Aim. To give students experience of researching important data and to conduct a policy-relevant negotiation exercise. Method. We created a classroom simulation in which students were required to research the debt positions of eight EU countries (Portugal, Ireland, Italy, Greece, Spain, Britain, France, and Germany) and then conduct a negotiation exercise with the goal of reducing the total debt burdens of the countries to which they were assigned. Results. Students discovered that a large amount of the EU debt burden can be written off by cross cancelling interlinked debt. Conclusion. As students were the focus of the exercise, their engagement and learning outcomes were high. The result is a platform to understand and discuss EU policy decisions and the wider implications of the debt crisis.